Analisis dan Perancangan Sistem Informasi Berbasis Website di Bebras Biro Universitas Dr. Soetomo - Mustafa, Zulfikar Amirul; Vitianingsih, Anik Vega; Kristyawan, Yudi; Lidya Maukar, Anastasia; Yasin, Verdi (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Universitas Dr. Soetomo holds a free challenge event every year. However, there is no application that helps with student data collection, activities and scoring assessment results because it still uses Microsoft Office Excel. In addition, there is no data processing such as graphs that report which schools each year participate in the competition and which students receive the highest scores in the free challenge. The Waterfall method is used to create a more organized web-based information system to overcome this problem. A clear framework is provided by this method from needs analysis to implementation. In addition to simplifying the registration and competition assessment process, this system provides educators, students and organizers with direct access to information. The results show increased efficiency, accessibility and transparency, and that this method helps improve quality and engagement in Bebras competitions. This shows that the appropriate use of information technology can significantly improve the quality of education.